The rehabilitation of Pestszentlőrinc city center: Heritage preservation and functional expansion; the reconstruction plan of the Rerrich legacy and the post-utilization concept of the former mining site - Szabó, Gyöngyvér (4D Journal of Landscape Architecture and Garden Art, 2010)
The area selected as the topic of the thesis is the currently changing new city centre of Pestszentlőrinc, the 18th District of Budapest, which centre is directly connected to Üllői Road. Thus the road functioning as the southeastern gate of the Capital serves as the traditional linear centre, the “high Street” of the district itself as well.
Keywords: Pestszentlőrinc; rehabilitation; functional expansion